Avaliação da usabilidade e manutenibilidade de modelos de processo de software em BPMN - Campos, André Luis Nogueira (2017)
A Software Process Model is a key element for the software improvement initiatives because Software Process Models materialize Software Engineering concepts and best practices that should be adopted throughout the software development lifecycle. Although initiatives such as CMMI-DEV and MR-MPS-SW have been proposed to improve Software Processes, only a few were found in the literature addressing the process modelling perspective. Moreover, those initiatives do not provide a detailed and systematic approach on how to define a body of knowledge for assessing the quality of process models based on international standards. In this work, we present a systematic approach to assess the quality of process models with respect to the usability and maintainability characteristics. The proposed solution defines processes for capturing Quality Measures(QMs) and Quality Measurement Elements(QMEs) for the chosen characteristics, based on a Literature Review and the ISO/IEC 25.000 standard, known as SQuaRE (Systems and software Quality Requirements and Evaluation). The work also defines a process on how to use QMs and QMEs to assess a given software process model, and executes this assessment process in a real-world scenario.